Pendidikan Keluarga Berbasis Gender Perspektif Pendidikan Agama Islam - Akhmad Fadli (Sekolah Tinggi Agama Islam Taruna Surabaya, 2020)
Abstract: Education is an activity carried out by humans where education has a broad scope. Education includes all experiences that exist in every human mind. Education is more pressing in terms of practices related to teaching and learning activities, besides that Education also focuses on thinking about education. Given the importance of parental role education in family education is also very important, where all children's knowledge and experience, both through vision, hearing, or behavior that comes from parents will influence the formation of children's personality, so parents should be able to educate her children, and the success of children in their future depends on how parents provide education. Likewise, the Gender Bias that exists in the family greatly affects the psychological condition of children in their lives in the future. Thus for the success of education in the family must be supported by Islamic religious education as a capital formation character that respects gender, and parents have a very important role in educating and directing their children, because if there is a gender bias in this family then this will greatly affect the mindset of their children in the future. Keywords : Family Education, Gender and PAI